Genome-based analysis of virulence determinants of a Serratia marcescens strain from soft tissues following a snake bite. (March 2018) - Huang, Yao-Ting; Cheng, Jan-Fang; Liu, Yi-Ting; Mao, Yan-Chiao; Wu, Meng-San; Liu, Po-Yu
Aim: Serratia marcescens wound infection after snakebite is often associated with aggressive presentations. However, the virulence determinants remain understudied.Materials & methods: Whole-genome sequencing was performed on S. marcescens VGH107, an isolate from wound infection secondary to Trimeresurus mucrosquamatus bite. Comparative genomics approach coupled with multivirulent-locus sequencing typing was applied to systematically predict potential virulence factors.Results: Multivirulent-locus sequencing typing indicated VGH107 falls within the cluster of high pathogenic strains. Comparative analysis identified virulence genes unique in VGH107, including ecpD and ecpE genes for periplasmic chaperone-pilus subunit complex and cdiA and cdiB genes for contact-dependent growth inhibition system.Conclusion: The data established here provide foundation for further research regarding the virulence and resistance of S. marcescens .